PERLINDUNGAN HUKUM TERHADAP PEKERJA WAKTU TERTENTU ATAS PEMUTUSAN HUBUNGAN KERJA KARENA ALASAN MANGKIR - Angelia, Ni Kadek Aprianty Ayu; Rr. Ani Wijayati; Jimmy Simanjuntak (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
One of the causes of termination of employment is the occurrence of work violations committed by workers / laborers or vice versa a company that is experiencing bankruptcy so that it must terminate the employment relationship (PHK) of its workers. The problem in this thesis is how is the legal protection for certain time workers who are terminated (PHK) for reasons of absenteeism? And how is the application of justice for workers who are terminated (PHK) for reasons of absenteeism related to the Central Jakarta District Court Decision Number 370/Pdt.Sus-PHI/2020/PN.Jkt.Pst?. This research uses normative legal research. This research was conducted or aimed only at written regulations or other legal materials. The legal materials used are primary legal materials and secondary legal materials. To obtain complete and accountable data, in normative legal research, data collection is carried out by library research. The legal materials that have been collected according to the formulation of the problem and the research theme are analyzed by referring to the qualitative analysis method. Legal protection aims to protect people who feel they have been harmed. If the worker is dismissed for reasons of absenteeism for more than 5 (five) consecutive days and the reason is correct because the worker has not been to work for more than 5 (five) consecutive days, then the worker is at fault because he has violated the laws and regulations. The action taken by the Defendant is to make the Plaintiff responsible for his actions so that no one imitates his actions.